IMPLEMENTATION OF EDUCATIVE ASSESSMENT IN PHYSICS EDUCATION STUDY PROGRAM UPH DURING ONLINE LEARNING - M.Si, Henni Sitompul; Sianipar, Lia Kristina; Martha, Kurniawati; Izaak, Maya P; Gunanto, Yohanes E (Polyglot, 2022)
Assessment is the collection of information about student learning outcomes. Educative assessment should enable students to respond as images of God and challenge them to grow and learn more. The purpose of this study is to describe the implementation of educative assessment in the Physics Education Study Program during the 2020/2021 academic year at the University of Pelita Harapan. This study used descriptive qualitative research methods. The Implementation of educative assessments were carried out through interdisciplinary assessment in some courses, mid-term and final-term personal reflections in all physics courses, vlogs in material physics courses as mid-term assessments, and used Moodle for review and weekly quizzes. Based on students’ feedback, it was known that the interdisciplinary assessment makes students understand the learning material deeper, more comprehensively, and integrated. The interdisciplinary assessment also makes the task load less overwhelming, especially during online learning. Vlogs as a mid-term assessment open space for students to be more creative and expressive to share knowledge in public, stimulate students' curiosity about learning material, and make students grow in their skills to find, summarize, and publish information digitally. At the end of the term, all of the students’ learning outcomes resulted in good and excellent grades. Bahasa Indonesia AbstrakPenilaian adalah pengumpulan informasi tentang hasil belajar siswa. Penilaian Edukatif memampukan siswa untuk merespon sebagai gambar Tuhan dan menantang mereka untuk tumbuh dan belajar lebih giat. Penelitian ini bertujuan untuk mendeskripsikan pengimplementasian penilaian edukatif pada Program Studi Pendidikan Fisika selama tahun ajaran 2020/2021 di Universitas Pelita Harapan dengan menggunakan metode penelitian deskriptif kualitatif. Penilaian edukatif dilakukan melalui penilaian interdisipliner pada beberapa mata kuliah, pembuatan refleksi pribadi pada tengah dan akhir semester pada semua mata kuliah fisika, Pembuatan vlog pada mata kuliah fisika material sebagai penilaian tengah semester, dan penggunaan moodle untuk review dan kuis mingguan. Berdasarkan umpan balik mahasiswa, diketahui bahwa penilaian interdisipliner membuat mereka memahami materi pembelajaran lebih dalam, lebih komprehensif dan terintegrasi. Penilaian interdisipliner juga membuat beban tugas tidak terlalu berat, terutama selama pembelajaran online. Pembuatan vlog sebagai penilaian tengah semester membuka ruang bagi mahasiswa untuk lebih kreatif dan ekspresif untuk berbagi ilmu di depan umum, merangsang rasa ingin tahu terhadap materi pembelajaran, dan menumbuhkan keterampilan mahasiswa dalam menemukan, merangkum, dan mempublikasikan informasi secara digital. Pada akhir semester, semua mahasiswa lulus dengan nilai yang baik dan sangat baik.